STUDI PAJANAN KADMIUM (Cd) PADA PEKERJA PENGECATAN MOBIL - Katharina Oginawati (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2005)
The paint contain heavy metals such as cadmium. The objective of this research are to obtain cadmium concentration of the paints that may be inhaled by workers. The result showed that in different colour and brands of paint contained cadmium level. There were 87,1% of respondents had the increases of cadmium concentration in their blood after spraying, between 2,508-33,53 μg/L. The increasing of Cadmium concentration in the blood are significant influenced by intake, age, water consumtion per day, fruit and vegetable consumtion, paint colour, and spraying done by the worker a day before. The mean of cadmium concentrations in their blood before spraying was 30,98 µg/L, after spraying was 40,71 μg/L and mean of cadmium concentrations in control population was 28,52 µg/L. Cadmium levels in blood of the sprayers and controls above OSHA cadmium level criteria, that is 5 μg/L. The mean of cadmium exposure during spraying was 0,12 µg/m3 (range 0–1,95 μg/m3) and the mean of cadimum exposure for 8 hours was 0,09 µg/m3 (range 0–1,46 µg/m3). These values still below Occupational Safety and Health Administration (OSHA) action level (2,5 µg/m3) and Permissible Exposure Level (PEL) (5 µg/m3). So, there are no acute cadimum exposures, but there are chronic cadmium exposures to the car panting workers.